The Implementation of the Problem-Based Learning Model to Improve the Learning Outcomes of Natural and Social Sciences (IPAS) for Grade IV Students of SDN 31 Cakranegara: Optional - Febrianti, Ana Ati; Hidayati, Vivi Rachmatul (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve the learning outcomes of Natural and Social Sciences (IPAS) through the implementation of the Problem-Based Learning model for Grade IV students of SDN 31 Cakranegara. The type of research used is classroom action research, with 25 students as the subjects of the study. The method used in this research was descriptive, with data collection techniques consisting of tests and observations. The results of the study show that, in Cycle I, 19 students achieved mastery while 8 students did not, and in Cycle II, 23 students achieved mastery while 2 students did not. The classical mastery learning rate of the students was 70% with a classical absorption rate of 76.4% in Cycle I. In Cycle II, the classical mastery learning rate was 92%, with a classical absorption rate of 91.6%. Based on the data analysis obtained from the implementation of actions from Cycle I to Cycle II, it can be concluded that the application of the Problem-Based Learning model can improve the learning outcomes of IPAS for Grade IV students of SDN 31 Cakranegara.